Draft Annual Plan 1999-2000 Government of Tripura - Planning Commission (Planning Commission, 1999)
Annual Plan - 1999-2000 - Proposed Outlay Draft Annual Plan 1999-2000 - Proposed Outlay Physical Targets and Achievements Statement Regarding Externally Aided Projects Centrally Sponsored Schemes Annual Plan - 1999-2000 - Basic Minimum Services - Outlay/Expenditure.
Government of Tripura, Planning Department